Pengaruh Literasi Keuangan, Financial Technology (Fintech) dan Gaya Hidup Hedonisme Terhadap Perilaku Keuangan Mahasiswa (Studi Kasus pada Mahasiswa Akuntansi Perguruan Tinggi Swasta di Kota Surakarta) - Sherly Arma Almiyani; Rispantyo Rispantyo (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of financial literacy, financial technology (fintech) and hedonistic lifestyle on the financial behavior of accounting students. The population in this study were accounting students at Private University in Surakarta City. The sample of this study was 83 students, obtained by the probability sampling method. Data were collected through questionnaires and analyzed using SPSS software version 27.0. Data analysis methods used in this study include descriptive statistics, validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of the linear regression analysis show that financial literacy and financial technology (fintech) have a positive and significant influence on students' financial behavior. Meanwhile, the hedonistic lifestyle has a negative and significant influence on students' financial behavior